Prevalence of multiple non-communicable diseases risk factors among self-reported healthy older adults living in community dwelling in India: Evidence from the Longitudinal Ageing Study in India - Shubhanjali Roy; Vansh Maheshwari; Saurav Basu (Elsevier, 2024)
Introduction: Noncommunicable disease (NCDs) risk factor clustering multiplies the risk especially in aging populations. The study objective was to estimate the prevalence and determinants of multiple NCD risk factors amongst older adults in India using the Community-Based Assessment Checklist (CBAC). Methods: A secondary analysis was undertaken using the Longitudinal Ageing Study in India (LASI) data wave-I having 40,510 participants aged ≥ 45 years without a history of diabetes or hypertension. The CBAC recommended by the national program consists of assesses six NCD risk factors: age, tobacco use, alcohol use, waist circumference, physical activity, and family history. Results: The prevalence of individuals at high-risk for NCDs defined as a CBAC score ≥ 4 was 55.2 % (95 % CI: 54.1, 56.29). Male gender, widowhood, obesity, and unemployment were independently associated with higher odds of having a high NCD risk factor status. Geographically, Northeastern and Southern states had higher burden of individuals at high-risk for NCDs. Furthermore, 28.44 % of patients at high-risk for NCDs were also having undiagnosed hypertension detected on screening. Conclusion: More than one in two older adults aged ≥ 45 years in India without an established history of diabetes or hypertension have four or more NCD related risk factors that accentuate their NCD risk.